A Demographic Analysis of Inguinal Hernia Patients: A Retrospective Study in Southern Karnataka - Wani, Umer Hamid; Alam, Saiyad Shah; Bhat, Beenish Bashir; Bhat, Ajaz Ahmad (Diversity: Disease Preventive of Research Integrity, 2025)
Hernias impose significant economic and physical burdens on patients, with inguinal hernias commonly linked to risk factors such as increased abdominal pressure, weak abdominal muscles, straining during defecation, heavy lifting, obesity, and pregnancy. This study aims to evaluate the prevalence of various types of inguinal hernias and identify associated risk factors in the southern Karnataka region. The study aimed to analyze the demographic characteristics of patients diagnosed with inguinal hernias. This is a retrospective study involving 160 cases reviewed at the NIUM Hospital. Data were collected from medical records and analyzed using SPSS software version 17 for Windows. The majority of patients (43.1%) were aged 41-60 years, with 98.1% being male. Common risk factors included heavy weight lifting (33.8%), benign prostate hypertrophy (28.8%), and abdominal muscle weakness (25.6%). Less common factors were smoking (32.5%), diabetes (11.9%), and family history (4.4%). Most hernias were indirect (69.8%) and on the right side (67.6%). Elective surgeries (94.4%) were more common than emergency procedures (5.6%), with open hernioplasty being the main operation (96.6%). Some patients had open herniorrhaphy (2.7%), and pediatric patients underwent open herniotomy (0.7%). These findings offer key insights into demographic trends, risk factors, and surgical outcomes of inguinal hernias, serving as a valuable reference for future research on their epidemiology and management.